How do we love? Romantic love style in men is related to lower testosterone levels - Babková Durdiaková, J; Celec, P; Koborová, I; Sedláčková, T; Minárik, G; Ostatníková, D (Physiological research, 2017)
Testosterone has been widely investigated in associations with many aspects of social interactions, emotions and behavior. No research has been conducted on its contribution to the variability of love styles in human. The aim of this paper was to uncover the possible relationship between not only the actual plasma testosterone levels, but also the prenatal testosterone level (expressed as 2D:4D ratio) and the sensitivity of androgen receptor and love typology in young healthy men. There are six love styles which are primary including Eros (passionate romantic love), Ludus (playful) and Storge (friendly) and secondary love consisting of Mania (obsessive), Pragma (practical realistic) and Agape (altruistic). Our results pointed out that low testosterone concentrations are associated with higher score for Eros, Ludus, Pragma, Mania love style. No significant association was proved for other tested parameters of androgenicity (2D:4D, sensitivity of androgen receptor) and love style after correction was applied. Different attitudes and behavior in relationships do have a biological foundation related to endogenous testosterone levels in plasma. Future studies should address questions about the family and social background of participants to differentiate here between moral rules or/and social-conventional rules.
Keywords: Male; mladý dospělý; Love; láska; prsty ruky; mužské pohlaví; emoce; Emotions; Interpersonal Relations; interpersonální vztahy; Fingers; Young Adult; testosteron; Humans; lidé; Testosterone